2008
DOI: 10.1007/s11244-007-9016-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct Solvothermal Formation of Nanocrystalline TiO2 on Porous SiO2 Adsorbent and Photocatalytic Removal of Nitrogen Oxides in Air over TiO2–SiO2 Composites

Abstract: Solvothermal decomposition of titanium(IV) tert-butoxide (TTB) in toluene at 573 K in the presence of silica gel (SiO 2 ) with continuous stirring yielded a titanium(IV) oxide (TiO 2 )-SiO 2 composite in which agglomerates of nanocrystalline TiO 2 were deposited on the surfaces of SiO 2 particles. Various TiO 2 -SiO 2 composites having different TiO 2 contents can be synthesized by changing the ratio of TTB and SiO 2 , and the composites had large surface areas corresponding to porous properties of SiO 2 . The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Typical preparation of titania-silica mixed oxides consists of the pre-hydrolysis of silica precursor (usually TEOS) in ethanol or isopropanol followed by the dropwise addition of titania precursor (Ti(OPr i ) 4 or TBOT) in acidic conditions. 24,40,[82][83][84][85][86][87][88][89] However, sol-gel reactions of silicate precursors are slow in ambient temperature conditions and do not guarantee complete hydrolysis and condensation of the reacting species, thus restricting the practical use of these mixed oxide materials. These concerns have been addressed by increasing the temperature and pressure by confining the reactants in a steel autoclave reactor to temperatures o250 1C for a period of up to 24 h. The hydrothermal synthesis (HTS) serves as a facile complementary step to ensure completion of the sol-gel reactions that result in uniform, well crystalline and thermally stable mixed oxide materials.…”
Section: Hydrothermal Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Typical preparation of titania-silica mixed oxides consists of the pre-hydrolysis of silica precursor (usually TEOS) in ethanol or isopropanol followed by the dropwise addition of titania precursor (Ti(OPr i ) 4 or TBOT) in acidic conditions. 24,40,[82][83][84][85][86][87][88][89] However, sol-gel reactions of silicate precursors are slow in ambient temperature conditions and do not guarantee complete hydrolysis and condensation of the reacting species, thus restricting the practical use of these mixed oxide materials. These concerns have been addressed by increasing the temperature and pressure by confining the reactants in a steel autoclave reactor to temperatures o250 1C for a period of up to 24 h. The hydrothermal synthesis (HTS) serves as a facile complementary step to ensure completion of the sol-gel reactions that result in uniform, well crystalline and thermally stable mixed oxide materials.…”
Section: Hydrothermal Synthesismentioning
confidence: 99%
“…The effect of the photocatalytic removal of nitrogen oxide pollutants from the air over TiO 2 -SiO 2 binary metal oxides was evaluated by Kominami et al 88 The results suggested that the crystallite size of TiO 2 and surface area of the photocatalyst were impetus for improved photoactivity. A control experiment was carried out to illustrate the significance of surface area on the photoactive TiO 2 .…”
Section: Gas Phase Reactionsmentioning
confidence: 99%
“…The specific physicochemical properties of solvents in these conditions can significantly improve the diffusion of chemical species and then markedly advance the nucleation and crystallization of desired phases. The products obtained by solvothermal synthesis usually show very interesting textural properties, superior thermal stabilities, well-controlled chemical composition, and characteristic morphologies which may provide higher potential for catalytic applications as compared to corresponding materials commercially available [19][20][21]. Solvothermal processes are commonly performed using stainless steel autoclave placed in electric oven.…”
Section: Introductionmentioning
confidence: 99%
“…O + e − −→ O − . (8) From the products of the reactions (5) and (8), the following combined reaction occurs:…”
Section: Oxidization Of Comentioning
confidence: 99%
“…Literature survey shows that TiO 2 photocatalyst combined with adsorbent such as activated carbon, zeolite, and silica (SiO 2 ) was mainly used in environmental purification technologies such as NO x removal [4][5][6], decomposition of acetaldehyde [7], dimethylsulfide [8], 2-propoanol [9], degradation of organophosphate and phosphonoglycine [10], and CO 2 reforming into fuel like CH 4 and CH 3 OH [11,12]. The CO oxidization by photocatalyst combined with FeO x , AL 2 O 3 , or CeO x and precious metal catalyst like Pt or Au was reported [13][14][15].…”
Section: Oxidization Of Comentioning
confidence: 99%